The Enemy Hates Best?: toxicity in League of Legends and Its Content Moderation Implications - Aguerri, Jesús C. (European journal on criminal policy and research, 2023)
In recent decades, many sectors of our society have been digitized, and much of our life has moved to cyberspace, especially in terms of entertainment. Users meet, relate, and cooperate in the new public space that is the internet and form digital communities. Video games play a leading role in the formation of such communities. However, these communities also present antisocial behaviors, ranging from disruptive actions to harassment and hate speech. Such behaviors, encompassed under the umbrella term toxicity, are a major concern for both users and those in charge of moderating these spaces. This article focuses on toxicity in today’s leading online video game League of Legends. Three hundred twenty-eight matches were reviewed using a system of two judges to study the prevalence of these problematic behaviors. We find that 70% of matches were affected by disruptive behavior. Nevertheless, only 10.9% of the analyzed matches were exclusively affected by downright harmful behavior. In our view, the results have relevant implications for content moderation policy that are also addressed in this paper.